2017
DOI: 10.1037/per0000169
|View full text |Cite
|
Sign up to set email alerts
|

Five-year prospective investigation of self-harm/suicide-related behaviors in the development of borderline personality disorder.

Abstract: Although borderline personality disorder (BPD) is frequently characterized by nonsuicidal self-injurious behavior (NSSI), suicide attempts (SA), suicidal ideation (SI), and/or suicide threats (ST), it is unclear whether these behaviors are precursors of BPD in adolescence. This study examined self-harm/suicide-related behaviors in the development of BPD from adolescence to adulthood in psychiatrically hospitalized adolescents. Participants were 116 adolescents consecutively admitted for a psychiatric hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…For instance, BPD features in adolescents have been related to clinically significant behaviors, such as suicidal thoughts and behaviors [e.g., 24]. Given the high prevalence of self-harm/suicide-related behaviors in the general adolescent population (mean lifetime prevalence of suicide-related behaviors =16.1%; [25]), and the fact that suicide-related behaviors may predict future PDs, life-threatening suicidal attempts have important implications for the conceptualization and treatment of PDs during early stages of the disorder, when targeted treatment is most effective [26].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, BPD features in adolescents have been related to clinically significant behaviors, such as suicidal thoughts and behaviors [e.g., 24]. Given the high prevalence of self-harm/suicide-related behaviors in the general adolescent population (mean lifetime prevalence of suicide-related behaviors =16.1%; [25]), and the fact that suicide-related behaviors may predict future PDs, life-threatening suicidal attempts have important implications for the conceptualization and treatment of PDs during early stages of the disorder, when targeted treatment is most effective [26].…”
Section: Introductionmentioning
confidence: 99%
“…Another recent longitudinal study examined self-harm and suicidal behaviors as predictors of the development of BPD 5 years later among adolescent psychiatric inpatients (Homan, Sim, Fargo, & Twohig, 2017). Findings suggested that only suicide threats uniquely predicted BPD 5 years later (Homan et al, 2017). As one of the key functions of emotions is to communicate, suicide threats may indicate a combination of high ED and deficits in communication skills, along with a learning history reinforcing emotional escalation.…”
Section: The Development Of Ed In Bpdmentioning
confidence: 99%
“…NSSI is purported to be a developmental precursor of BPD pathology under the biosocial developmental model [16, 26, 2830]. Though previous pivotal studies have mainly focused on the cross-sectional associations of NSSI and BPD in adolescent samples [1623, 30], longitudinal associations between NSSI and suicide attempts to other mental disorders in adolescents [8, 31, 32], adulthood-spanned BPD samples or retrospective adult data [7, 10], and longitudinal assessment of suicidal behaviours to BPD [24, 3336].…”
Section: Introductionmentioning
confidence: 99%
“…Though previous pivotal studies have mainly focused on the cross-sectional associations of NSSI and BPD in adolescent samples [1623, 30], longitudinal associations between NSSI and suicide attempts to other mental disorders in adolescents [8, 31, 32], adulthood-spanned BPD samples or retrospective adult data [7, 10], and longitudinal assessment of suicidal behaviours to BPD [24, 3336]. Thus, NSSI as a developmental precursor of BPD, which requires longitudinal assessment of at least two time points, remains largely underexamined [3, 7, 18, 26, 37, 38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation